Its What’s on the Inside That Counts: An Effective, Efficient, and Streamlined Method for Quantification of Octocoral Symbiodiniaceae and Chlorophyll - Steinberg, Rosemary Kate; Johnston, Emma L.; Bednarek, Teresa; Dafforn, Katherine A.; Ainsworth, Tracy D. (Frontiers in Marine Science, 2021)
Ocean warming driven bleaching is one of the greatest threats to zooxanthellate cnidarians in the Anthropocene. Bleaching is the loss of Symbiodiniaceae, chlorophyll, or both from zooxanthellate animals. To quantify bleaching and recovery, standardised methods for quantification of Symbiodiniaceae and chlorophyll concentrations have been developed for reef-building scleractinian corals, but no such standard method has been developed for octocorals. For stony corals, quantification of Symbiodiniaceae and chlorophyll concentrations often relies on normalisation to skeletal surface area or unit of biomass [i.e., protein, ash-free dry weight (AFDW)]. Stiff octocorals do not change their volume, as such studies have used volume and surface area to standardise densities, but soft-bodied octocorals can alter their size using water movement within the animal; therefore, Symbiodiniaceae and chlorophyll cannot accurately be measured per unit of surface area and are instead measured in units of Symbiodiniaceae and chlorophyll per μg of host protein or AFDW. Though AFDW is more representative of the full biomass composition than host protein, AFDW is more time and resource intensive. Here, we provide a streamlined methodology to quantify Symbiodiniaceae density, chlorophyll concentration, and protein content in soft-bodied octocorals. This technique uses minimal equipment, does not require freeze-drying or burning samples to obtain ash weight, and is effective for down to 0.2 g wet tissue. Bulk samples can be centrifuged, the Symbiodiniaceae pellet washed, and the supernatant saved for protein analysis. This efficient technique allows for clean, easy to count samples of Symbiodiniaceae with minimal animal protein contamination. Chlorophyll a and c2 extractions occurs at different rates, with chlorophyll a taking 24 h to extract completely at 4°C and chlorophyll c2 taking 48 h. Finally, we found that where necessary, wet weight may be used as a proxy for protein content, but the correlation of protein and wet weight varies by species and protein should be used when possible. Overall, we have created a rapid and accurate method for quantification of bleaching markers in octocorals.